2021
DOI: 10.1021/acssuschemeng.1c01012
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Microwave Synthesis of Mesoporous Oxygen-Doped g-C3N4with Carbon Vacancies for Efficient Photocatalytic H2O2Production

Abstract: Oxygen-doped g-C 3 N 4 (CN) with carbon vacancies (O−CNC) was synthesized by microwave heating the mixture of melamine−cyanuric acid (MCA) supramolecular aggregates and oxalic acid for only 7 min. The as-synthesized O−CNC shows a mesoporous structure and exhibits a tunable band structure, optimized charge separation, and significantly enhanced twoelectron reduction for H 2 O 2 production. The photocatalytic H 2 O 2 production rate reaches 2008.4 μmol h −1 g −1 under simulated sunlight irradiation, which is mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
56
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(57 citation statements)
references
References 49 publications
1
56
0
Order By: Relevance
“…Among all the doping elements, nonmetal oxygen doped g-C 3 N 4 is one of the effective ways to extend the visible-light absorption and regulate the intrinsic electronic characteristics and band structure of g-C 3 N 4 , thereby leading to an enhancement of its photocatalytic activities. [26][27][28] Recent reports have revealed that a higher photocatalytic H 2 production can be achieved by co-doping of binary nonmetal atoms into the lattice of g-C 3 N 4 , such as C, O co-doped g-C 3 N 4 , 29 B, O co-doped g-C 3 N 4 , 30 P, O co-doped g-C 3 N 4 , 31 and N, O co-doped g-C 3 N 4 . 32 In addition, S, O co-doped g-C 3 N 4 was fabricated via one-step thermal condensation of a mixture of urea and thiourea and was employed as an efficient photocatalyst in the degradation of neonicotinoid insecticides in water.…”
Section: Introductionmentioning
confidence: 99%
“…Among all the doping elements, nonmetal oxygen doped g-C 3 N 4 is one of the effective ways to extend the visible-light absorption and regulate the intrinsic electronic characteristics and band structure of g-C 3 N 4 , thereby leading to an enhancement of its photocatalytic activities. [26][27][28] Recent reports have revealed that a higher photocatalytic H 2 production can be achieved by co-doping of binary nonmetal atoms into the lattice of g-C 3 N 4 , such as C, O co-doped g-C 3 N 4 , 29 B, O co-doped g-C 3 N 4 , 30 P, O co-doped g-C 3 N 4 , 31 and N, O co-doped g-C 3 N 4 . 32 In addition, S, O co-doped g-C 3 N 4 was fabricated via one-step thermal condensation of a mixture of urea and thiourea and was employed as an efficient photocatalyst in the degradation of neonicotinoid insecticides in water.…”
Section: Introductionmentioning
confidence: 99%
“…Considering their respective characteristics, researchers propose various semiconductor-based photo-Fenton systems for effective degradation of refractory environmental contaminants 1,7 Among all the photocatalysts, graphitic carbon nitride (g-C 3 N 4 ), as a nonmetallic conjugated photocatalyst, attracts wide attention owing to its chemical stability, appropriate band gap energy, and unique electronic structure. [13][14][15] However, it is still limited by the low surface area, visible light utilization, blocked charge separation, and low quantum efficiency 16,17 and thus needs further modification. In terms of photocatalyst modification, the coupling of a semiconductor with transition metal-based materials can enhance its activity in photocatalytic and oxygen reducing reactions as well as charge separation and transfer ability, extend the light absorption range, and activate photocatalytic reactions for remarkable degradation performance.…”
Section: Introductionmentioning
confidence: 99%
“…Various strategies have been devoted to overcoming these drawbacks through tuning the photocatalytic and electronic properties of pristine CN, including heteroatom doping, , heterojunction, , and rational morphological or topological design. , As the electron transport between the nitrogen atom and the carbon atom in pristine CN is limited, doping metal heteroatoms or nonmetal heteroatoms ,, are known as an effective method to improve the photocatalytic performance of CN by distinctly adjusting its energy band structure, photoabsorption region, electronic conductivity, and charge transfer mobility. ,, Nonmetal atom doping has received extensive interest compared to metal atom doping because it could result in the formation of various conjugated triazine structures in the modified CN molecules. ,, As reported, , certain nonmetal atoms prefer the specific substitutional position of CN. In particular, phosphorus and bromine atoms prefer to substitute the nitrogen atoms, while oxygen and sulfur atoms are prone to displace the carbon atoms in pristine CN .…”
Section: Introductionmentioning
confidence: 99%